Progress in field experimentation for environmentally sustainable tourism – A knowledge map and research agenda. (February 2023) - Demeter, Csilla; Fechner, David; Dolnicar, Sara
Abstract: The global aspiration to mitigate climate change puts substantial pressure on the tourism sector – one of the most polluting industries – to operate in more sustainable ways. This study reviews intervention experiments in tourism and hospitality aimed at making tourist behaviour more sustainable. The analysis of 53 field experiments reveals the most promising intervention strategies. The resulting knowledge map highlights that past intervention studies were limited to only a small number of relevant target behaviours and intervention types, pointing to many unexplored areas that require urgent attention in future.